Mothers Do Not Show Increased Offspring Avoidance and Elevated Corticosterone Levels during Weaning Conflict in Rats. - Charlotte Cox; Reinmar Hager (PLoS ONE, 2016)
Parent-offspring conflict is predicted to occur because offspring will demand more parental investment than is optimal for the parent, and is said to be strongest during weaning when parents reduce nursing while offspring continue to demand parental care. While weaning conflict has been shown to be stressful in offspring, little is known about the effects of weaning conflict on mothers. We hypothesized that during weaning mothers have higher levels of stress hormone (corticosterone) compared to early lactation because of increased offspring demand. Further, we predicted that if mothers are given the option to avoid offspring solicitation they would do so and show lower corticosterone levels. We tested our hypotheses in an experimental population of rats in which one group of females was given the opportunity to avoid offspring solicitation. We measured faecal corticosterone metabolite levels using a non-invasive approach, and maternal and offspring behaviours during weaning. In contrast to our predictions, we detected lower levels of corticosterone metabolites during weaning than before, irrespective of cage type. Further, during weaning mothers did not show increased offspring avoidance behaviour although offspring solicitation increased significantly. Our results therefore cast doubt on the generally accepted notion of weaning conflict as a stressful period for mothers characterized by overt offspring solicitation.